Skin and Mucosal Damage in Patients Diagnosed With COVID-19: A Case Report - Singh, Charleen (J Wound Ostomy Continence Nurs, 2020)
Patients admitted to the intensive care unit (ICU) are at a high risk for developing pressure injuries. A patient requiring multiorgan support is at a higher risk for pressure injuries related to immobility, sedation, vasopressors, and hypoxia. To mitigate pressure injuries, our hospital utilizes a bundle approach to prevent skin injury. However, despite efforts to prevent pressure injuries, we found our patients in the ICU with the diagnosis of COVID-19 went on to develop significant pressure and mucosal injuries. This is a case report of 4 patients diagnosed with COVID-19 who developed significant skin and mucosal injuries during their ICU admissions in the month of March 2020. We found that patients developed skin conditions that were initially thought to be deep-tissue injuries (DTIs) early in the admission. The DTIs progressed over the course of the admission in the ICU and evolved to thick adherent eschar that appeared to be unstageable pressure injuries, which extended beyond the soft tissue directly over the bony prominence. We also found that skin damage to the mucosa of the nares, tongue, lips, and urethra presented first as inflammation and then progressed to thick eschar. Despite maximum pressure relief with the use of a pressure-relieving turn and position system, bordered foam dressings, fluidized positioners, specialty beds, and leadership support for twice-a-week skin checks, our patients diagnosed with COVID-19 developed extensive skin damage across the fleshy portion of the buttocks and on the mucosa of the nares, tongue, lips, and urethra during minimal exposure to pressure. Although the initial presentation of the skin damage appeared to be related to pressure, the extent of the skin damage suggests a vascular inflammatory process beyond skin damage related to pressure.